Effect of miR-488 on Colon Cancer Biology and Clinical Applications. (5th May 2022) - Wu, Liangqin; Li, Songguo; Shu, Peng; Liu, Qian
Abstract : Objective . To explore the expression levels of miR-488, miR-29c-3p, and growth differentiation factor 15 (GDF15) in colon cancer tissue and analyze their relationship with clinicopathological features in patients with colon cancer. Methods . The study was conducted from November 2012 to November 2020. A total of 200 patients with colon cancer were treated in our hospital during this period. During the operation, the colon cancer tissues and the adjacent tissues whose distance from the cancer tissues were more than 5 cm were collected, and the expression levels of miR-488, miR-29c-3p, and GDF15 mRNA in colon cancer tissues were detected by qRT-PCR (real-time fluorescence quantitative). The relationship between them and the clinicopathological features and prognosis of patients with colon cancer were analyzed and discussed. Results . The level of miR-488 in colon cancer tissues was lower than that in adjacent tissues, but the levels of miR-29c-3p and GDF15 mRNA in colon cancer tissues were higher than those in adjacent tissues (P < 0.05 ). Compared with paracancerous tissues, the expression rates of miR-29c-3p and GDF15 protein were higher in colon cancer tissues (P < 0.05 ). There was no difference in age, sex, tumor location, and tumor diameter between high expression of miR-488 group and low expression of miR-488 group (P > 0.05 ). The degree of differentiation, depth of invasion, TNM stage, lymph node metastasis, and other factors have a direct impact on the level of miR-488 and the expression of miR-29c-3p (P < 0.05 ). The depth of invasion, TNM stage, and lymph node metastasis could affect the expression of GDF15 in patients with colon cancer (P < 0.05 ). Conclusion . miR-488, miR-29c-3p, and GDF15 in colon cancer tissue are related to the clinicopathological features of patients in varying degrees and may become markers after early warning of colon cancer, which can provide effective guidance for clinical diagnosis and treatment.